2022
DOI: 10.18632/aging.203984
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A-related genetic variants protect against Alzheimer’s disease

Abstract: The Apolipoprotein E ( APOE ) genotype has been shown to be the strongest genetic risk factor for Alzheimer’s disease (AD). Moreover, both the lipolysis-stimulated lipoprotein receptor (LSR) and the vascular endothelial growth factor A (VEGF-A) are involved in the development of AD. The aim of the study was to develop a prediction model for AD including single nucleotide polymorphisms (SNP) of APOE , LSR and VEGF-A-related variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Interestingly, recent evidence suggests mutations of VEGF-A protect against Alzheimer’s disease. 21 Two epistatic interactions, each between VEGF-A related single nucleotide polymorphisms identified in large-scale GWAS studies (143 Alzheimer’s disease cases and 180 controls), were the strongest protective factors against Alzheimer’s disease in the absence of ε4 APOE allele, which remained the most significant genetic predisposition. 21 This study suggests that VEGF-A signaling may play a more significant role than previously indicated in the pathogenesis of Alzheimer’s disease.…”
Section: Aberrant Vegf Signaling In Alzheimer’s Diseasementioning
confidence: 98%
“…Interestingly, recent evidence suggests mutations of VEGF-A protect against Alzheimer’s disease. 21 Two epistatic interactions, each between VEGF-A related single nucleotide polymorphisms identified in large-scale GWAS studies (143 Alzheimer’s disease cases and 180 controls), were the strongest protective factors against Alzheimer’s disease in the absence of ε4 APOE allele, which remained the most significant genetic predisposition. 21 This study suggests that VEGF-A signaling may play a more significant role than previously indicated in the pathogenesis of Alzheimer’s disease.…”
Section: Aberrant Vegf Signaling In Alzheimer’s Diseasementioning
confidence: 98%
“…In contrast, the 3’UTR lengthening DAG set was significantly enriched for ErbB, brain-derived neurotrophic factor, circadian rhythm, EGF/EGFR, and insulin signaling pathways (Figure 8D and 8E). Of note, studies have already linked these pathways to AD pathogenesis, but none have looked at these pathways from an APA-centric perspective (6776). These results lay the preliminary groundwork for future studies to dissect the mechanism by which dysregulated APA drives AD pathobiology.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF inhibits CXCL1 via endothelial Cdk5 activity VEGF signaling is markedly reduced in the brain with aging, while increasing VEGF signaling protects against age-related capillary loss, compromised perfusion, and reduced tissue oxygenation 18 , which are also observed in AD patients [47][48][49] . Moreover, VEGF in CSF is associated with longitudinal memory performance, particularly in amyloid and Tau positive individuals 50 , and VEGF-related variants might appear to in uence the risk for AD 51 . Therefore, these reports suggested that VEGF signaling is involved in the development of AD.…”
Section: Discussionmentioning
confidence: 99%